The Effect of E-LKPD Assisted PJBL-STEM Learning Model on Scientific Reasoning Ability and Argumentation Performance of Class XII Science Students in Renewable Energy Materials - Melania Sandri Ayuni; I Wayan Distrik; Viyanti Viyanti (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
This research aims to analyze and prove the influence of scientific reasoning ability and argumentation performance of students who follow the PjBL-STEM learning model assisted by e-LKPD with conventional models in learning Physics class XII IPA SMAN 15 Bandar Lampung. The research design was quasi-experimental (quasi-experimental), and the pretest posttest design was used. The population in this study were all students of class XII IPA. The research sample was determined by random sampling technique. The sample in this study was XII IPA 1 as the control class and class XII IPA 3 as the experimental class. Data was collected using test questions, questionnaire sheets and observation sheets. Hypothesis testing using t test and Manova test. The results showed that there was an effect of scientific reasoning ability and student argumentation performance between students who took the PjBL-STEM learning model assisted by e-LKPD and students who followed the conventional learning model based on the results of the Manova test with an F value from Wilks' Lambda. = 43.208 and the significance value = 0.000. Based on these results, it can be concluded that there is an influence of scientific reasoning ability and argumentation performance of students who follow the PjBL-STEM learning model assisted by e-LKPD with conventional learning models in learning Physics class XII IPA SMA Negeri 15 Bandar Lampung.